Communicating Between Species and Between Disciplines—Lessons from the Old English Seafarer. (2nd October 2018) - Ellard, Donna Beth
ABSTRACT: This article examines the analogy of birdsong in the Old English Seafarer as an access point for critical and meta-critical discussions regarding the communicative prohibitions and possibilities between birds and humans, literary criticism, and the biosciences. It argues that while the seafarer initially hears the calls of birds within the analogical framework of birdsong, on the ocean such a position is short-lived. The seafarer recalibrates his sense of sound and of song to that of motion, entraining and then attuning his entire motional self to a rhythmic mode of listening. As he "listens" with his body, the seafarer forecloses analogical similarities between his voice and those of birds and participates in an embodied form of bird–human communication that extends entrainment and attunement towards an ethical posture. The Seafarer 's imaginary encounter between birds and humans serves as a model for actual ones. The article argues that embodied listening permits non-analogical moments of bird–human communication and diminishes the communicative barriers between literary criticism and bioscientific research. Turning away from analogy loosens the prohibition on interspecies and interdisciplinary communiqués and permits an "ethics of attunement" to emerge between species and disciplines.